2005
DOI: 10.1111/j.1532-7795.2005.00098.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Shifts in Parent and Peer Influences on Boys' Beliefs About Delinquent Behavior

Abstract: This paper examines the relative shifts in parent and peer influences on the development of boys' beliefs regarding delinquency from early to middle adolescence. The paper also explores the influence that beliefs about delinquency have on subsequent changes in these social relationships. Structural equation modeling is used to analyze six annual waves of data for 481 boys from the youngest sample of the Pittsburgh Youth Study. Increased parentadolescent conflict only predicted changes in beliefs about delinque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
2
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 69 publications
2
60
2
6
Order By: Relevance
“…Individuals who receive less parental monitoring and control are more likely to acquire delinquent attitudes and to engage with delinquent peers, and are therefore more likely to engage in delinquent behavior (Sutherland 1947). Previous research indeed indicated that adolescents who received more effective parenting are less likely to have delinquent attitudes and delinquent peers (Knoester and Haynie 2005;Pardini et al 2005;Warr 2005). In a study examining the 'gender gap' in violent delinquency, Heimer and Coster (1999) found however, that more indirect parental control, i.e., bond with parents, reduced definitions favorable to violence among girls and not boys.…”
Section: Sex Differences In Indirect Pathways From Parenting To Delinmentioning
confidence: 94%
“…Individuals who receive less parental monitoring and control are more likely to acquire delinquent attitudes and to engage with delinquent peers, and are therefore more likely to engage in delinquent behavior (Sutherland 1947). Previous research indeed indicated that adolescents who received more effective parenting are less likely to have delinquent attitudes and delinquent peers (Knoester and Haynie 2005;Pardini et al 2005;Warr 2005). In a study examining the 'gender gap' in violent delinquency, Heimer and Coster (1999) found however, that more indirect parental control, i.e., bond with parents, reduced definitions favorable to violence among girls and not boys.…”
Section: Sex Differences In Indirect Pathways From Parenting To Delinmentioning
confidence: 94%
“…Existing evidence suggests that adolescents with predispositions to delinquency are more likely to engage in delinquent behavior (Moffitt and Caspi 2001). The general assumption is that an increase in tolerance towards delinquency often precedes the initiation of delinquent acts (Pardini et al 2005). Evidence also indicates that the influence of attitudes on behavior may be contingent upon a number of covariates, including the mental health status of the youth (Nebbitt et al 2008).…”
Section: Attitudes Towards Deviance and Antisocial Behaviormentioning
confidence: 98%
“…Several longitudinal studies have shown that increases in peer delinquency are significantly related to more tolerant beliefs about the acceptability of antisocial behavior, including causing serious harm to others (Henry et al, 2000;Pardini, Loeber, & Stouthamer-Loeber, 2005). In fact, the impact of deviant peers on IC may be stronger than family influences during adolescence, as youth begin spending more time with friends (Larson & Richards, 1991) and begin receiving positive reinforcement from peers for committing interpersonally callous acts (Dishion, McCord, & Poulin, 1999 is associated with high levels of IC in early adolescence, particularly among youth with elevated conduct problems (Kimonis et al, 2004).…”
Section: Peer Influence and Icmentioning
confidence: 99%